Penetration of Amoxicillin into Cerebrospinal Fluid - Strausbaugh, Larry J. (1978)
The penetration of amoxicillin into cerebrospinal fluid (CFS) in the presence of meningeal inflammation was evaluated in patients with tuberculous meningitis. Serum and CSF concentrations of amoxicillin were measured at 2 h in nine patients who received a 1-g oral dose and at 1.5 and 4 h in ten patients who received a 2-g intravenous injection of sodium amoxicillin. After the oral dose, CSF concentrations ranged from 0.1 to 1.5 μg/ml. After the intravenous injection, CSF concentrations ranged from 2.9 to 40.0 μg/ml at 1.5 h and from 2.6 to 27.0 μg/ml at 4 h. These data on penetration suggest that parenterally administered sodium amoxicillin may be of value in the therapy of acute bacterial meningitis.